2021
DOI: 10.1016/j.intimp.2021.107493
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2: Insight in genome structure, pathogenesis and viral receptor binding analysis – An updated review

Abstract: The novel coronavirus disease (COVID-19) a global pandemic outbreak is an emerging new virus accountable for respiratory illness caused by SARS-CoV-2, originated in Wuhan city, Hubei province China, urgently calls to adopt prevention and intervention strategies. Several viral epidemics such as severe acute respiratory syndrome coronavirus (SARS-CoV) in 2002 to 2003 and H1N1 influenza in 2009 were reported since last two decades. Moreover, the Saudi Arabia was the epicenter for Middle East respiratory syndrome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 85 publications
0
27
0
Order By: Relevance
“…A recent report demonstrated acts as an antagonist of interferon (IFN) and viral encoded repressor of RNA interference 47 . Previous studies also reported N protein help package encapsidated genome into virions via binding Nps3 48 . Also, mutations were note in Nsp3 and Nsp5 which play role in blocking host innate immune response, promoting cytokine expression and inhibiting IFN signaling.…”
Section: Discussionmentioning
confidence: 92%
“…A recent report demonstrated acts as an antagonist of interferon (IFN) and viral encoded repressor of RNA interference 47 . Previous studies also reported N protein help package encapsidated genome into virions via binding Nps3 48 . Also, mutations were note in Nsp3 and Nsp5 which play role in blocking host innate immune response, promoting cytokine expression and inhibiting IFN signaling.…”
Section: Discussionmentioning
confidence: 92%
“…Flavonoids such as quercetin, naringin, hesperetin, and catechin possess a higher grade of antiviral activity and they act by affecting the replication and infectivity of certain RNA and DNA viruses [ 125 ]. Recently, during this COVID-19 pandemic, there is an overwhelming scientific interest in searching for naturally occurring and synthetic flavonoid compounds to reduce COVID-19-infected cardiovascular malfunctioning by blocking the viral entry at the ACE2 receptor [ 126 ].…”
Section: Therapeutic Approaches and Future Drug Discoverymentioning
confidence: 99%
“…The positive‐sense ssRNA SARS‐CoV‐2 virus has a genome of about 29,700 nucleotides with 79.5% identity to SARS‐CoV‐1. Its genome encodes four main structural proteins; spike protein, membrane protein, nucleocapsid protein, and the envelope protein 6 , 7 . SARS‐CoV‐2 binds to angiotensin‐converting enzyme 2 (ACE2) via the (receptor‐binding domain) RBD of its spike protein that protrudes from the viral envelope.…”
Section: Introductionmentioning
confidence: 99%